A novel multi-modular series HVDC tap - Tang, Yunpeng; Watson, Alan James; Wheeler, Patrick; Farr, Ewan; Feldman, Ralph (2017)
Tapping energy from a HVDC transmission line to serve small remote communities has been considered by researchers and HVDC manufacturers since the 1960s. Many HVDC taps proposed consider the performance of diodes, Thyristors and GTOs and the utilization of bulky and expensive high voltage transformers. This paper proposes a novel HVDC tap topology, the n-phase multi-modular series tap (MMST), which utilises capacitors to decouple HV voltage and IGBT H-bridge sub-modules typically found in modular multilevel converters to transfer HVDC to MVAC. The number of phases and operating frequency can be picked according to the requirement of the application. The feasibility of n-phase MMST has been verified by the results from simulation carried out in PLECS software.